Optimum Selection of Direct-Coupled Photovoltaic Pumping System in Solar Domestic Hot Water Systems - Al-Ibrahim, Abdulrahman M. (University of Wisconsin-Madison, 1997)
The performance of photovoltaic powered pumps in direct and indirect solar domestic hot water (PV-SDHW) systems has been studied. The direct PV-SDHW system employs a photovoltaic array, a DC-motor, a centrifugal pump, a thermal collector, and a storage tank. The indirect PV-SDHW system employs similar components to those in the direct PV-SDHW system in addition to a heat exchanger to transfer the energy from the collector-loop fluid to the tank-loop fluid. Both a forced convection heat exchanger and a natural convection heat exchanger were investigated. The primary objective of this thesis is to optimize the design and quantify the performance of PV- SDHW systems. The search methodology for an optimum PV-SDHW system has been performed in a unique two-phase procedure. In phase one the goal is to find, among the possible PV pumping systems' flow rate profiles, the profile that maximizes the performance of a given SDHW system. In phase two the goal is to select the components of the PV pumping system. Each combination of PV cells, DC-motor and pump exhibits a unique flow rate profile. Therefore, the problem in this phase is to identify the PV pumping system components that results in the best match to the optimum flow rate profile found in phase one. This decoupling considerably eased the process of optimal search. An analysis of actual flow rate profiles of PV pumping systems showed that the optimum search can be restricted to the family of profiles represented by a function dependent upon three parameters only. A comparison is made between the performance of the optimum direct PV-SDHW system and a conventional direct SDHW system operating under three control schemes: an ON-OFF flow SDHW system operating at the manufacturer's recommended constant flow rate, an ON-OFF flow SDHW system operating at the optimum constant flow rate and a linear proportional flow SDHW system, with the flow proportional to the solar radiation operating under an optimum proportionality. It was found that the optimum direct PV-SDHW system was superior to the systems with conventional control schemes.
Under the supervision of Professors William Beckman and Sanford Klein; 215pp.
Keywords: Thesis (Ph.D.)--University of Wisconsin--Madison, 1997.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.